Strong metal–support interactions between Ni and ZnO particles and their effect on the methanation performance of Ni/ZnO. Issue 19 (5th September 2017) - Wang, Weixing; Li, Xuekuan; Zhang, Ye; Zhang, Rong; Ge, Hui; Bi, Jicheng; Tang, Mingxing
Abstract : Strong metal–support interactions (SMSI) between Ni and ZnO particles and their suppression effect on CO methanation. Abstract : A Ni/ZnO system was prepared by coprecipitation and characterized after reduction at different temperatures (350, 400, 450 and 500 °C) using TG-MS, H2 -TPR, N2 physisorption, XRD, SEM, H2 and CO chemisorption, TEM, EPR and XPS. H2 and CO chemisorption experiments combined with XRD, SEM and TEM analyses showed evidence for strong metal–support interactions (SMSI) between Ni and ZnO particles, and the degree of SMSI strengthened as the reduction temperature rose. TEM, EPR and XPS studies revealed that the generation of SMSI was attributed to the geometric decoration of Ni particles by ZnO and electron transfer from ZnO to Ni atoms as well as the chemical interaction between Ni and ZnO leading to the formation of a NiZn alloy. Methanation of CO was used as a probe reaction to characterize the effect of SMSI on the catalytic performance of Ni/ZnO. The results showed that SMSI in general had a remarkable suppression effect on the methanation activity, but a light-degree SMSI state facilitated enhancement of the selectivity and stability of CO methanation. Interestingly, the suppressed activity can also be restored with different degrees via re-oxidization and re-reduction treatments under mild conditions. The discovery of SMSI between Ni and ZnO gives a new understanding of the interaction between Ni and supports, and provides a way to tune the interaction between Ni and supports as well as a way to regulate the methanation performance of the Ni/ZnO catalyst or Ni-based catalysts.